Constructing the Framework for Robotics Waqf Fatwa: Contemporary Islamic Jurisprudential Foundations for Accelerating Autism Therapy - Hammad, Hamza Abed Alkarim (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2026)
The rapid integration of artificial intelligence technologies within the global medical landscape has precipitated significant discursive tensions in contemporary Islamic jurisprudence, particularly concerning the ethical boundaries and legal legitimacy of using anthropomorphic robots for highly complex therapeutic purposes. Robotic technologies, such as the NAO model, have been shown to play a crucial role in clinical interactions for children with autism. However, current muʿāmalah (Islamic transactional and social law) literature shows a profound analytical deficit concerning the validity of waqf (charitable endowment) for movable assets that visually intersect with the prohibition of showing animate beings, or taṣwīr (the representation or depiction of living beings). Therefore, this study aims to reconstruct legal reasoning that systematically synchronizes classical philanthropic doctrines with cutting-edge medical technology innovations through a Maqāṣid al-Sharīʿah (the objectives of Islamic law) approach and a comprehensive uṣūliyyah (principles of Islamic legal methodology) analysis of contemporary fatwā (authoritative legal opinions) consensuses. The results showed that the procurement and waqf ofanthropomorphic robots are Sharīʿah-compliant, based on the extension of qiyās (analogical reasoning) to pedagogical instruments and the principle of maṣlaḥah mursalah (unrestricted public interest), particularly in the protection of intellect and life. These considerations are prioritized over classical textual constraints, thereby offering a transformative legal-ethical framework capable of accommodating rapid medical-technological advancement to achieve sustainable human welfare in the digital era.